2012
DOI: 10.1063/1.4705469
|View full text |Cite
|
Sign up to set email alerts
|

rf-power and the ring-mode to red-mode transition in an inductively coupled plasma

Abstract: The optical output of an alkali-metal inductively coupled plasma (alkali-ICP) plays an important role in both atomic magnetometers and atomic clocks, producing these devices’ atomic signals through optical pumping. Unfortunately, though the alkali-ICP’s optical pumping efficiency grows exponentially with temperature, at relatively high temperatures (∼140 °C) the discharge transitions from “ring mode” to “red mode,” which is a spectral change in the plasma’s output that corresponds broadly to a transition from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…5 2 S 1/2 transition). 22 As we raised the temperature of the discharge, entering the ring-mode to red-mode transition region, we found that the discharge could exhibit self-sustained oscillations as illustrated in Fig. 5 (Multimedia view).…”
Section: Observations Of Icp Self-pulsingmentioning
confidence: 88%
See 3 more Smart Citations
“…5 2 S 1/2 transition). 22 As we raised the temperature of the discharge, entering the ring-mode to red-mode transition region, we found that the discharge could exhibit self-sustained oscillations as illustrated in Fig. 5 (Multimedia view).…”
Section: Observations Of Icp Self-pulsingmentioning
confidence: 88%
“…Evidence suggests that the ring-mode to red-mode transition is driven by radiation trapping. 22 FIG. 1.…”
Section: B the Ring-mode To Red-mode Transitionmentioning
confidence: 96%
See 2 more Smart Citations
“…As discussed in [30], rf-power has a significant influence on the lamp's average temperature. In addition, rf-power affects the lamp's temperature gradient, thereby defining the location of the liquid Rb pool in the lamp, and hence the Rb vapor pressure [31].…”
Section: Testing the Nic Mechanismmentioning
confidence: 99%